2019
DOI: 10.1371/journal.pone.0221327
|View full text |Cite
|
Sign up to set email alerts
|

Continuity of care for newly diagnosed diabetic patients: A population-based study

Abstract: This study explores whether continuity of care is associated with health care outcomes and medical care use among patients with newly diagnosed diabetes. A retrospective cohort analysis was performed using the Taiwanese National Health Insurance database, and cases were followed up from January 2010 to December 2012. Four thousand and seven patients with newly diagnosed diabetes were followed for 3 years. The continuity of care was measured using the continuity of care index (COCI) and the usual provider conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Explanations for why a certain method was used were rarely provided. Two studies used multiple continuity of care calculations and the findings were consistent among different measurements [ 45 , 56 ]. Among studies that assessed the effect of continuity of care by categorization, there was no consistent definition for cut-off.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Explanations for why a certain method was used were rarely provided. Two studies used multiple continuity of care calculations and the findings were consistent among different measurements [ 45 , 56 ]. Among studies that assessed the effect of continuity of care by categorization, there was no consistent definition for cut-off.…”
Section: Resultsmentioning
confidence: 81%
“…Details of the definitions and formulae of all continuity of care measurement tools used in the reviewed studies are listed in Additional file 2 . The two most frequently used continuity of care instruments were the continuity of care index (CoCI) (20 studies) [ 7 , 10 , 13 , 18 , 25 , 26 , 29 , 33 , 39 41 , 45 , 47 , 53 56 , 59 61 ] and usual provider continuity index (UPCI) (12 studies) [ 27 , 36 – 38 , 42 , 44 , 45 , 48 , 49 , 52 , 56 , 58 ]. CoCI measures the dispersion of visits of a patient to different providers [ 63 ], which is calculated by , where k is the number of providers, is the number of visits to provider i and N is the total number of visits of the patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Switzerland, the study of Frei et al 2013 also found no association with consultation count, which might be due to the fact that in Switzerland a structured invitation mechanism for follow-up appointments is uncommon. Another known factor associated with increased quality of diabetes care is continuity of care [37,38]. We did not explicitly measure continuity of care, but we found a negative association between number of treating GPs and all three process indicators, and a negative association with the outcome indicator of cholesterol.…”
Section: Plos Onementioning
confidence: 74%
“…Therefore, the accessibility and opportunity of social participation for social network and social support become very important. Patients with newly diagnosed diabetes in Taiwan were 61 years old on average with the standard deviation of 10 years [ 56 ], suggesting a substantial need for elderly social services. This study chimed harmoniously with the above-mentioned advocacies and demonstrated the importance of ESS densities on DRPH rates.…”
Section: Discussionmentioning
confidence: 99%